Genome-wide analysis of the 4-Coumarate-CoA ligase gene family in wheat: Expression patterns under salt stress and light-regulated cold acclimation - Fatemeh Gholizadeh; Gabriella Szalai; Tibor Janda (Plant Stress)
The 4-coumarate-CoA ligase (4CL) gene family plays a fundamental role in the phenylpropanoid pathway, influencing plant growth, lignin biosynthesis, and stress adaptation. Despite its significance, the 4CL gene family in wheat (T. aestivum L.) has not been extensively studied. This study identified 40 Ta4CL genes distributed across 20 chromosomes, characterizing their structural features, phylogenetic relationships, and subcellular localization. Promoter analysis revealed cis-regulatory elements linked to stress response, hormone signaling, and light regulation. Gene expression analysis demonstrated that specific Ta4CL genes, such as Ta4CL8–5A and Ta4CL4–7D, were significantly upregulated under high salinity conditions, indicating their role in salt tolerance. Additionally, light-regulated cold acclimation experiments showed differential expression of multiple Ta4CL genes, with Ta4CL2–6D and Ta4CL3–6B displaying notable induction under blue light and cold stress. Protein interaction analysis highlighted the involvement of Ta4CLs in lignin and flavonoid biosynthesis, particularly through interactions with phenylalanine ammonia-lyase and other key enzymes in the phenylpropanoid pathway. Physiological assessments confirmed that Na+ accumulation and the Na+/K+ ratio were correlated with the expression of specific Ta4CL genes, reinforcing their functional role in stress adaptation. These findings provide valuable insights into the diverse roles of 4CL genes and offer potential targets for breeding stress-resilient wheat cultivars.